Analisis Faktor-Faktor yang Mempengaruhi Audit Delay pada Pemerintahan Provinsi Sumatera Selatan - Dhea Tasyania Ramadhani; Sulaiman Sulaiman; Nurhasanah Nurhasanah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to determine the effect of government size, level of regional independence, audit findings, re-election of regional heads and leverage on audit delay in the South Sumatra provincial government. The data collection technique used in this study is to use secondary data in the form of an Examination Result Report (LHP) and a list of regional heads issued by the Minister of Home Affairs. The data of this study were analyzed using multiple linear regression analysis using the IBM SPSS Version 25 software. The results of this study indicate that the size of the government, the level of regional independence, audit findings, re-election of regional heads and leverage simultaneously have no effect on audit delay. Partially the level of regional independence has a significant effect on audit delay while the size of the government, audit findings, re-election of regional heads and leverage have no effect on audit delay of the South Sumatra provincial government.